2020
DOI: 10.1128/msystems.00382-20
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Structure-Based Repositioning of Approved Drugs for Spike Glycoprotein S2 Domain Fusion Peptide of SARS-CoV-2: Rationale from Molecular Dynamics and Binding Free Energy Calculations

Abstract: The membrane-anchored spike (S) protein of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has a pivotal role in directing the fusion of the virus particle mediated by the host cell receptor angiotensin-converting enzyme 2 (ACE-2). The fusion peptide region of the S protein S2 domain provides SARS-CoV-2 with the biological machinery needed for direct fusion to the host lipid membrane. In our present study, computer-aided drug design strategies were used for the identification of FDA-approved small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Further, N-protein's structural study reveals that the residues of CTD are involved in RNA-binding and amino acid residues between 248-270 positions are essential for nucleotide-binding [ 20 ]. Computational aided drug designing has led to the identification of various targets and rapidly screening their possible inhibitors without much economic and resources burden in the shortest time possible [ 26 , 27 ]. Various in vitro clinically relevant models are also developed that can help in testing potential drug candidates against the novel targets to support the findings of the in silico studies [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, N-protein's structural study reveals that the residues of CTD are involved in RNA-binding and amino acid residues between 248-270 positions are essential for nucleotide-binding [ 20 ]. Computational aided drug designing has led to the identification of various targets and rapidly screening their possible inhibitors without much economic and resources burden in the shortest time possible [ 26 , 27 ]. Various in vitro clinically relevant models are also developed that can help in testing potential drug candidates against the novel targets to support the findings of the in silico studies [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The potential lipids‐binding residues in FP of SARS‐CoV‐2 is centralized amid in Lys790, Thr791, Lys795, Asp808, and Gln872 residues, contributing to lipid interaction and penetration. 48 Surface models predicted that the FP of SARS‐CoV‐2 S was organized in a more compact conformation than that of SARS‐CoV S. 49 Cleavage at S2′ exposes the FP domain, which, in turn, inserted in the host membrane triggering the viral fusion. 22 With strong membrane‐perturbing capacities, 50 FP plays a crucial role in cell fusion.…”
Section: Molecular Characteristics Of the Sars‐cov‐2 Spike(s) Proteinmentioning
confidence: 99%
“…An in silico study to repurpose FDA-approved drugs as SARS-CoV2 spike protein inhibitors via virtual screening revealed that the potent compounds bind at the RBD-ACE2 interface involving diverse amino acids (319–530) of SARS-CoV2 spike protein. A detailed analysis of interface residues revealed that a stretch of the SARS-CoV2 spike protein (339–506) to be interacting majorly with the ACE2 (340–468) and hence, the same site was chosen for docking based screening of milk peptides [ 21 ].…”
Section: Resultsmentioning
confidence: 99%